OPEC and the world's energy future : its legacy and promise - Alsahlawi, Mohammed A., 1954- (Boca Raton, FL : CRC Press, 2021)
"This work offers a complete account of OPEC's past, present, and possible future in relation to economic, political, and technological changes. It focuses on the impacts of recent international political and economic developments and analyzes factors affecting OPEC as well as the world oil market. The book describes the continued importance of oil and gas as major sources of energy throughout the world. It examines OPEC's history and merits, highlights differences among OPEC members, and discusses OPEC's relations with the world. It spends considerable time on concentrating on the impact of new technologies and how they may challenge and change the organization in the near and long term"--
Pre-OPEC -- OPEC evolution -- OPEC finds its way -- Internal rivalry -- External conflicts -- Saudi Arabia vs the US -- Energy and technology -- Technology effects -- The economics of energy technology -- Energy technology mix and future energy -- The economics of renewable energy -- Economics of unconventional oil and gas technologies -- Economics of energy demand technologies -- Economics of energy efficiency technologies -- Changes and challenges -- Forces at work -- Challenges to OPEC -- OPEC's strategies -- OPEC future -- Energy future -- OPEC gloomy future -- A world without OPEC -- Qatar and natural gas -- Oil spill in the Gulf -- Kuwait oil fires -- Oil price crashes -- OPEC and Iran-Iraq war -- Coronavirus (COVID-19) -- What is the point of OPEC -- Energy future.
OCLC-licensed vendor bibliographic record.
Keywords: Organization of Petroleum Exporting Countries -- History; Petroleum industry and trade; International agencies; International trade; Cartels; Energy policy; TECHNOLOGY / Petroleum; BUSINESS & ECONOMICS / Industries / Energy Industries